Pemanfaatan Endocarpium Buah Kenari (Canarium indicum L.) Menjadi Briket Dan Validasi Poster Edukasi Bagi Masyarakat - Hasanudin, Mahyono; Tolangara, Abdulrasyid; Majid, Ilham; Alting, Ummi Kalsum (Universitas Khairun, 2024)
Walnuts are a native Indonesian plant that grows widely in eastern Indonesia such as North Sulawesi and North Maluku. In biology, the walnut shell is called the endocarpium and acts as a fuel substitute for kerosene. Currently, endocarpium is unused waste, so it is necessary to process it into a useful product with high economic value, in the form of briquettes as an alternative fuel. The aim of this research is to describe the use of walnut endocarpium as briquettes and to describe the results of validation of learning posters in the community. The research was carried out for 3 months, June to August 2023 and took place in the biology laboratory of FKIP Unkhair for the process of cleaning the endocarpium, drying, carbonization and making briquettes. The research results show that the endocarpium of walnuts from Makian Island can be used to make briquettes with a height of 5 cm and a diameter of 16 cm. Empirical test results show that using 2 briquettes can boil 300 ml of water in 1.38 seconds. The poster validation results are categorized as valid to very valid, and suitable for use as learning media in the community.